Nationalism in the Lyrics of "Lil Waṭan" by Mashrou’ Leila: A Structuralist Analysis - Muhammad Mahdi; Viyan Sutobri; Ida Nursida; Dadang Ismatullah (Journal of Arabic Literature (JaLi), 2025)
Literature serves as a profound reflection of life, articulating values, emotions, and social criticism through aesthetic language. In the modern era, song lyrics have evolved into a potent medium for conveying ideological messages and challenging the status quo. This study investigates the song "Lil Waṭan" by Mashrou’ Leila, a prominent Lebanese alternative-rock band celebrated for their progressive stance on identity and politics. Unlike traditional patriotic anthems, "Lil Waṭan" offers a sharp counter-discourse, critiquing the manipulation of nationalist sentiment by authoritarian powers to suppress dissent. Utilizing a descriptive qualitative method grounded in Claude Lévi-Strauss’s structuralist theory, this research analyzes the lyrics as a system of signs to uncover the underlying binary oppositions and social myths embedded within the text. The analysis reveals that the song’s structure is built upon deep tensions between the citizenry and the ruling authority, specifically manifesting through the binary oppositions of "love versus fear" and "genuine nationalism versus false nationalism." The findings demonstrate how the text exposes specific "patterns of silencing," including the use of propaganda to fabricate external conspiracies, the "anesthetization" of the public through ideological lethargy, and the deployment of mass entertainment—symbolized by the command to "dance"—as a distraction from political stagnation. By deconstructing these symbols, the study concludes that Mashrou’ Leila redefines patriotism not as blind submission, but as a critical consciousness that rejects the commodification of the "homeland" for social control. Ultimately, this research highlights how contemporary Arab music functions as a sophisticated literary site for political resistance and social critique